STRUCTURAL DESIGN AND EXPERIMENTAL ANALYSIS OF ADJUSTABLE 3-DOF VIBRATING SCREEN - HAN Meng; GONG ZhiQiang; WANG ChengJun (Jixie qiangdu)
Aiming at the problems of screen blinding, low screening efficiency and unstable screening performance of traditional vibrating screen in agricultural field, a three degree of freedom adjustable vibrating screen was designed, including leveling device, two degree of freedom excitation system, single degree of freedom excitation system, controller and level monitor.The two degree of freedom excitation system provides reciprocating movement along the x-axis and rotation around the y-axis for the screen disk, while the single degree of freedom excitation system provides reciprocating movement along the y-axis for the screen disk, and the two are connected in series to form a three degree of freedom excitation device.The kinematics simulation of the vibrating screen was carried out by using ADAMS software to verify that the vibrating screen can vibrate with 1～3 degrees of freedom; Based on the discrete element method, the screening process of rice particles on the adjustable three degree of freedom vibrating screen plate was simulated and analyzed, and the experiment was carried out on the prototype.The results show that the screening efficiency of three degree of freedom vibration is 8.8% and 33.4% higher than that of two degree of freedom and single degree of freedom vibration respectively, which solves the problems of less degree of freedom, low screening efficiency and unstable screening performance of traditional vibrating screen.